Pengaruh Penggunaan Kredit Usaha Rakyat, Komitmen Organisasi dan Penggunaan Informasi Akuntansi terhadap Kinerja Usaha UMKM - Widyawati, Luh Made; Yudantara, I Gede Agus Pertama (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
This research was conducted with the aim to determine the effect of the use of people's business credit, organizational commitment and the use of accounting information on business performance. This research is a quantitative study using a questionnaire and the measurement technique used is the Likert scale. This research was conducted in Buleleng District. The sampling technique in this study was purposive sampling, so a sample of 146 respondents was obtained. The data obtained were analyzed using several data analysis techniques with statistical tests using the SPSS computer program version 22.0. After conducting various statistical tests along with the hypothesis testing using the t statistical test, the results of the t test explained that each of the variables of the use of people's business credit (X1), variable organizational commitment (X2) and the variable use of accounting information (X3) had a positive effect on business performance. This means that the higher the use of people's business credit, organizational commitment and the use of accounting information, the higher the business performance.